Global transcriptomic analysis of Francisella tularensis SchuS4 differentially expressed genes in response to doxycycline or ciprofloxacin exposure - Galia Zaide; Inbar Cohen-Gihon; Ohad Shifman; Ofir Israeli; Moshe Aftalion; Sharon Maoz; Theodor Chitlaru; Raphael Ber; Anat Zvi; Ida Steinberger-Levy (BMC Genomic Data, 2023)
Abstract Objective As part of a research aiming at presenting an alternative approach for rapid determination of antimicrobial susceptibility by quantification of changes in expression levels of specific marker genes and gene sets, cultures of the virulent bacterial strain Francisella tularensis SchuS4 were grown in the presence of inhibitory/sub-inhibitory concentrations of either ciprofloxacin or doxycycline and their transcriptomic profiles were elucidated using differential expression analysis followed by functional annotation. Data description RNA sequencing was performed to identify differentially expressed genes (DEGs) in response to exposure of F. tularensis SchuS4 to either ciprofloxacin or doxycycline, the antibiotics of choice for Tularemia therapy. Accordingly, RNA samples were collected 2 h post antibiotic exposure and subjected to RNA sequence analysis. Transcriptomic quantification of RNA representing duplicated samples generated highly similar gene expression data. Exposure to sub-inhibitory concentration [0.5 x MIC (minimal inhibitory concentration)] of doxycycline or ciprofloxacin modulated the expression of 237 or 8 genes, respectively, while exposure to an inhibitory concentration (1 x MIC) resulted in the modulation of 583 or 234 genes, respectively. Amongst the genes modulated upon doxycycline exposure upregulation of 31 genes encoding for translation-functions could be distinguished, as well as downregulation of 14 genes encoding for functions involved in DNA transcription and repair. Ciprofloxacin exposure impacted differently the RNA sequence profile of the pathogen, resulting in upregulation of 27 genes encoding mainly DNA replication and repair functions, transmembrane transporters and molecular chaperons. In addition, 15 downregulated genes were involved in translation processes.